Second‐Harmonic Generation via Nonlinear Raman–Nath Diffraction in an Optical Fibonacci Superlattice. Issue 3 (2nd January 2022) - Chen, Yesheng; Liu, Yongxing; Zhao, Ruwei; Xu, Tianxiang; Sheng, Yan; Xu, Tiefeng
Abstract: Nonlinear Raman–Nath diffraction is an effective method for frequency conversion in the presence of phase mismatch. In a structure featuring periodically modulated quadratic nonlinearity, the available frequency‐doubled patterns generated from nonlinear Raman–Nath diffraction constitute uniformly spaced points due to the one parametric decided reciprocal lattice vectors. Herein, nonlinear Raman–Nath second‐harmonic generation from the optical Fibonacci superlattice is theoretically investigated, and a propagation equation that describes the properties of frequency‐doubled waves is presented. Abundant diffraction peaks that are substantially more varied than the traditional Raman–Nath regime are observed. The dependence of the generated second‐harmonic signals on the structural parameters and fundamental laser performance is also comprehensively discussed. Abstract : The frequency‐doubling process via nonlinear Raman‐Nath diffraction in nonlinear optical Fibonacci superlattice is theoretically investigated. Broadband second‐harmonic waves covering large emission angle range with numerous peaks are comprehensively discussed. The obtained findings provide an improved understanding of the nonlinear optical Fibonacci superlattice and predict potential applications of transverse phase‐matched second‐harmonic generations.